Bancos digitais: fatores que influenciam na satisfação dos clientes em Parintins - Ribeiro, Andreina de Souza (Brasil, 2025)
This work's main theme is the banking service offered by 100% digital banks, and aims to analyze the extent to which the services offered by the digital bank Nubank influence the satisfaction of Parintins customers. The methodology, according to its objectives, is characterized as descriptive research, quantitative in nature and which will use survey research. During data collection, a questionnaire was used, which was applied to users of Nubank digital bank services. As for the analysis of the collected data, it was done through descriptive statistical analysis. The main sources for the research were the FEBRABAN research on banking technology and the author JEHNIFFER (2021). This research sought to identify the services offered by the Nubank digital bank; characterize customers from Parintins who use digital banking services and also describe the factors that influence customer satisfaction. This work is relevant for financial institutions that intend to develop and improve services to improve the quality of service, in addition to recruiting new customers, focusing on satisfaction with the services offered.